Produk Pembiayaan Lembaga Keuangan Syariah Berbasis Akad Ijarah - Arik Hermawan (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2025)
Abstract: The Ijarah contract is one of the primary instruments in Islamic finance that is used for leasing transactions, serving as a Sharia-compliant alternative to conventional lease agreements. Derived from the Arabic word